The complete mitochondrial genome of the Arctic fairy shrimp Branchinecta paludosa (Müller, 1788) (Anostraca, Branchinectidae) from Sirius Passet, North Greenland - Ji-Hoon Kihm; Euna Jo; Tae-Yoon Park; Bo-Mi Kim (Biodiversity Data Journal, 2022)
Here we report the complete mitochondrial genome of the Arctic fairy shrimp, Branchinecta paludosa (Müller, 1788) (Anostraca, Branchinectidae), which was collected in the High Arctic of North Greenland. A complete 16,059 bp mitochondrion of B. paludosa was sequenced and assembled with the Illumina next generation sequencing platform. The B. paludosa mitogenome contains 13 PCGs, 22 tRNAs and 2 rRNA genes that are commonly observed in most metazoans and shows the conserved gene arrangement pattern of Anostraca. Our results of the phylogenomic analysis are consistent with the previous phylogenetic relationship, based on nuclear 18S ribosomal DNA. The B. paludosa mitogenome will be useful for understanding the geographical distribution and phylogenetic relationship of anostracans.